Intraocular Pressure Measurement Using Ocular Response Analyzer, Dynamic Contour Tonometer, and Scheimpflug Analyzer Corvis ST - Lisa Ramm; Robert Herber; Eberhard Spoerl; Frederik Raiskup; Lutz E. Pillunat; Naim Terai (Journal of Ophthalmology)
Purpose. To compare intraocular pressure (IOP) measurements with Goldmann applanation tonometry (GAT), ocular response analyzer (ORA), dynamic contour tonometer (DCT), and Corvis ST (CST) in healthy subjects. Methods. In a prospective, observational study, IOP measurements with GAT (GAT-IOPc), ORA (IOPcc), DCT (DCT-IOP), and CST (bIOP) were performed and analyzed in 94 healthy subjects. Results. Mean age of the participants was 45.6 ± 17.2 years (range 18 to 81 years). Mean GAT-IOPc was 12.9 ± 2.4 mmHg, mean DCT-IOP was 16.1 ± 2.6 mmHg, and mean IOPcc was 15.6 ± 3.3 mmHg. DCT-IOP and IOPcc were significantly higher than GAT-IOPc (P<0.001). Mean bIOP was 13.5 ± 2.4 mmHg that was slightly higher but not significantly different from GAT-IOPc (P=0.146). Correlation analysis of IOP values and central corneal thickness (CCT) revealed a negative correlation between GAT-IOPc and CCT (r = −0.347; P=0.001). However, IOPcc, DCT-IOP, and bIOP showed no significant correlation to CCT. Only bIOP revealed a weak but significant age dependency (r = 0.321, P=0.002). Conclusion. All tonometry devices showed a good agreement of biomechanical corrected IOP values with GAT-IOPc. As no influence of CCT on IOPcc, DCT-IOP, and bIOP was detectable, the used correction algorithms appear to be appropriate in these tonometers in the clinical setting. The highest agreement was found between GAT-IOPc and bIOP. However, bIOP weakly correlated with participants’ age. Further studies are needed to elucidate the role of bIOP for IOP measurement.